An inflated subpolar gyre blows life toward the northeastern Atlantic. (September 2016) - Hátún, H.; Lohmann, K.; Matei, D.; Jungclaus, J.H.; Pacariz, S.; Bersch, M.; Gislason, A.; Ólafsson, J.; Reid, P.C.
Graphical Abstract: Highlights: We investigate the impact of the North Atlantic subpolar gyre variations on zooplankton. The focus is on the Irminger Sea and the south Iceland shelf region and on sub-decadal time scale. A northeastward extension of the subpolar gyre limb enriches the biological production. Driving mechanisms are: deep mixing, frontal shifts and advection. The marked "high-or-low" variability in this region might be predicted more than a year in advance. Abstract: Deep convection in the Labrador and Irminger Seas inflates the cold and low-saline subpolar gyre, which is a rich nutrient and zooplankton source for the surrounding warmer waters of subtropical origin. The zooplankton abundances on the south Iceland shelf show characteristic sub-decadal variability, which closely reflect the oceanic abundances of the ecologically most important zooplankton species – Calanus finmarchicus. Much higher abundances of this species are observed during years when the winter mixed layer depths (MLD) in the Labrador-Irminger Sea, and over the Reykjanes Ridge are deep. Furthermore, a tight relationship is identified between on-shelf zooplankton abundances and lateral shifts of the biologically productive subarctic front southwest of Iceland. Thus, we suggest that northeastward expansion of the subpolar gyre results in biologically productive periods in the waters southwest of Iceland – both oceanic and on the shelf. In addition to local atmospheric forcing, we find that the MLD and frontal position are also impacted by remote heat losses and convection in the Labrador Sea, through northward advection of unstable mode waters. The sub-decadal oceanic and on-shelf biological production peaks are possibly predictable by half a year (local winter convection to subsequent summer production), and the advective time-lag from the Labrador Sea might induce an even longer predictability horizon (up to 1.5 years).